Language Department on feelings and speaking output of Intensive French I students of the Bachelor of Arts in Modern Languages: Specialization in French and English, School of Arts and Sciences, University of El Salvador, semester I-2019.semester I-2019 - Rivas Melara, Guillermo Josué; Mena Ayala, Augusto Adalberto; Carpio Martínez, José Luis (2024)
The current topic research is presented by undergraduate students of Modern Languages Major: French and English, as final investigation work of graduation. This research has for tittle: “The impact of the attitude of adjunct professors of the foreign language department on the feelings and speaking output of Intensive French I students of the bachelor of arts in modern languages: specialization in French and English, school of arts and sciences, university of El Salvador, semester i-2019”.Professional attitude of a teacher during teaching in class-room can judged from his personality, knowledge, communication and management skills Improvement in competencies of teacher is either possible when a teacher properly planned for teaching, maintain class-room environment and maintain personality (Chek, & Khan, A., Khan, S., Khan, S.Z., & Khan, M. (June, 2016). Impact of teacher personality on the academics of the students. Journal of Physical Education Research, Volume 3, Issue II, 74-79). The research has the principal purpose to examine the different environments showed in Intensive French I class by adjunct professors ́ attitude and how the speaking output and feelings could be impacted during this process. The group intends to investigate in a deeper way the relation between professor/student within the French class as beginners in the language, the environment and different opinions presented by both parts.